Application of Axiomatic Design approach to reduce coupling and repetition in the UCAV conceptual design process - M.A. shahi-Ashtiany; F. Shahmiri; A.R. َAlipour (مهندسی مکانیک شریف, 2021)
Generally, there are different challenges in traditional approaches to aircraft design, resulting in a decrease in the efficiency of the design process. For instance, decisions made at the conceptual design phase are based on limited knowledge about design, while these decisions can significantly decrease the design freedom in further design steps. In addition, the decision in the conceptual design phase constituted as high as 80% of the life-cycle costs. Furthermore, in the conceptual design phase, because of their critical issues in achieving performance requirements, more attention has been given to aerodynamics and propulsion disciplines, while other disciplines are evaluated only later throughout the design process. However, in the last decades, new requirements such as environment-friendliness, considering global warming, reducing energy consumption, reusing, recycling, and remanufacturing have been added to aircraft design criteria. These changes in design requirements have led to the development of different kinds of Functional Requirements (FRs) and disciplines and, consequently, increased coupling and iterative cycles. These issues have increased the complexity of the aircraft conceptual design process compared to the past. Consequently, in the last decades, many researchers and designers have tried to address these challenges. In this regard, various design methodologies such as multidisciplinary design optimization and knowledge-based engineering were developed. These approaches could support the evolutionary improvement of current product designs or the study of the novel complex product or could reduce the coupling between various FRs and Design Parameters (DPs). In this research, designers tried to use the Axiomatic Design (AD) approach to identify and reduce coupling between different FRs, resulting in less repetitive activities and design iteration in the design process. The authors also developed an algorithm based on the AD method to improve the conceptual aircraft design. The results obtained in this study indicate the high efficiency of this method in reducing the coupling between the FRs defined for the aircraft as well as in reducing repetitive activities, thus optimizing the time and the cost of the aircraft design process.